PROSES IMITASI ANAK TERHADAP LAGU DEWASA MELALUI NEW MEDIA - Heri Hadiyanto; Ida Ri'aeni (JIKE: Jurnal Ilmu Komunikasi Efek, 2020)
There are many mass media that can be accessed, including being accessed through television, radio, mobile phones (smartphones) and the internet, as well as the role of the closest environment in influencing children's behavior. Based on this phenomenon, children tend to like adult songs, and memorize the pronunciation of the lyrics. The study was conducted on elementary school students in SD Negeri 17 Kuningan, West Java. This study aims at 1) to find out the stimulus factors in children in the process of imitation of adult songs, and 2) to find out cognitive and affective in children in the process of imitation of adult songs. The method used for this study is a qualitative approach with a case study tradition, in this research is to find out approaches or searches that aim to explore and understand a central phenomenon. Data collection techniques are carried out by observation, interviews, and documentation. While for data analysis using triangulation techniques. Based on the results of the study show that: 1) stimulus factors in children in the process of imitation of adult songs in Kuningan 17 Public Elementary School: (a) social media, the tendency to listen to adult songs via YouTube and Instagram and the duration that children need among them ? 1 hour, 1- 3 hours, and ? 3 hours. (b) mass media, children watch adult songs through television from advertisements, and concerts. (c) non-media / environment, children affected by adult songs through family, relatives, peers, the environment around the residence, and encouragement to know. (d) social media that is accessed, all children tend to often use YouTube, and other social media in accessing adult songs. 2) cognitive and affective factors in children in the process of imitation of adult songs in Kuningan 17 Public Elementary School: (a) cognitive, children tend to be exposed to adult songs from their closest environment, driven by personal curiosity, until finally memorized, but children do not understand the meaning and the meaning of the song in question. (b) affective, various reasons for their liking Korean songs, solely for purely entertainment rather than based on wishing for the praise of others. From the results of cognitive and affective processes found the types of children that are classified in imitating adult songs. (c) behaviorism / konatif, positive and negative effects of liking adult songs, especially Korean songs. Keywords: Imitation Children Process, New Media, Adults Song, K-Pop Songs, S-R Theory.